Anna Komnene : the life and work of a medieval historian - Neville, Leonora Alice (Onassis series in Hellenic culture, 2016)
The authorial persona constructed by Anna Komnene in her Alexiad (a history of her father the Byzantine Emperor, Alexios Komnenos, 1081-1118) responded to the challenges Byzantine culture created for female historical authorship. Fundamental cultural conceptions of masculinity, femininity, authority, deference, and morality within Byzantine society worked to make history writing an activity for men. Once the masculinity of history writing is understood, we can see how Anna endeavored to construct herself as both an authoritative historian and a meritorious woman